PENERAPAN MODEL PEMBELAJARAN JIGSAW DENGAN MEDIA VISUALISASI CANDI UNTUK MENINGKATKAN KESADARAN SEJARAH DAN PRESTASI BELAJAR IPS KELAS VIIA SMP N 2 SAMBIREJO TAHUN 2014/2015 - Rumhmiyati, R.; Suryani, Nunuk; Sariyatun, S. (HISTORIKA, 2016)
The research aims to uncover effektiveness application of learning models jigsaw with temple visualization media to raise awareness of history and learning achievements of students. This research as classroom action research. The obyect of research is the Class VIIA that consist of 25 students. The data collecting that are use by documents, structure observing, quisener and objective test. Based on the analysis of cycle I, II and III can be concluded application of learning models jigsaw with temple visualization media can be increase awareness of history and learning achievement of student. The average prosentage of awareness of history was increase from 79,17 % to the firts cycle, 82,98% % at second cycle and 83,73% at third cycle. And the average of learning achievements score was increased from 66,16 in the first cycle , 75,52 at second cycle and 80,64 at the third cycle. Based on the result could be concluded that application of learning models jigsaw with temple. visualization media can increased awareness of history and learning achievements of students class VIIA SMP N 2 Sambirejo Year 2014/2015.